Sensory Characteristics and Lactic Acid Content of Cassava Leaf Fermentation Using Microbial-Nutrient - Yusni Khairani Tampubolon; Winda Fransisca Saragih; Fuad Hasan; Muhammad Amran; Adanan Purba (Jurnal Peternakan Integratif, 2025)
Cassava leaves have a potential to be an alternative feed as it has high crude protein content, as well as essential vitamins and minerals. This research aims to find the effective combination dose of inoculant and nutrient additive in improving sensory characteristics and lactic acid in fermented cassava leaves (Manihot esculenta). This study used four treatments and five replications. T0 (Fresh cassava leaf without additives), T1 (fermentation with 40% EM4, 20% ml Viterna, and 40% ml MOL), T2 (20% EM4, 40% Viterna, and 40% MOL), and T3 (40% EM4, 40% Viterna, and 20% ml MOL). All additives were applied at a total dose of 0.5% (v/w) to the fresh weight of the material, and fermented anaerobically for 14 days. Data were analyzed using analysis of variance based on a Completely Randomized Design and Duncan's test. The results showed that T3 produced the highest lactic acid content (P <0.05) compared to other treatments. Treatments T2 and T3 produced a brownish-yellow silage color that was significantly different (P<0.05) from treatments T0 and T1, which showed a yellowish green color. The aroma produced in T2 and T3 was moresour (P<0.05) than T0. The treatment did not have a significant effect on silage texture (P>0.05). The combination of inoculants and nutrient additives had a significant effect (P<0.05) on the mold coverage score, with a tendency for a decrease in the mold coverage score from T1 to T3. It was concluded that The combination of inoculants and nutrient additives can improve the quality of cassava leaf fermentation. The best result is obtained in T3 which produces the highest lactic acid content and improved sensory characteristics.